2021
DOI: 10.7554/elife.67604
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological rescue of impaired mitophagy in Parkinson’s disease-related LRRK2 G2019S knock-in mice

Abstract: Parkinson’s disease (PD) is a major and progressive neurodegenerative disorder, yet the biological mechanisms involved in its aetiology are poorly understood. Evidence links this disorder with mitochondrial dysfunction and/or impaired lysosomal degradation – key features of the autophagy of mitochondria, known as mitophagy. Here, we investigated the role of LRRK2, a protein kinase frequently mutated in PD, in this process in vivo. Using mitophagy and autophagy reporter mice, bearing either knockout of LRRK2 or… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
82
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 82 publications
(86 citation statements)
references
References 68 publications
3
82
1
Order By: Relevance
“…This effect was specific for inhibition of LRRK2, as neither GZD-824 or GSK3357679A impacted basal mitophagy in LRRK2 knock-out cells. Consistent with previous work [ 25 ], basal mitophagy was lower in LRRK2[G2019S] MEFs compared with wild-type MEFs and treatment with Type I or Type II inhibitors increased basal mitophagy to levels similar to those observed in LRRK2 knock-out cells ( Figure 8A,B ).…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…This effect was specific for inhibition of LRRK2, as neither GZD-824 or GSK3357679A impacted basal mitophagy in LRRK2 knock-out cells. Consistent with previous work [ 25 ], basal mitophagy was lower in LRRK2[G2019S] MEFs compared with wild-type MEFs and treatment with Type I or Type II inhibitors increased basal mitophagy to levels similar to those observed in LRRK2 knock-out cells ( Figure 8A,B ).…”
Section: Resultssupporting
confidence: 92%
“…Previous work revealed that pathogenic LRRK2[G2019S] mutation significantly reduces basal mitophagy, but not general autophagy, in primary MEFs and various mouse tissues in a manner that is rescued by inhibiting LRRK2 with structurally distinct and selective Type I inhibitors, GSK3357679A and MLi-2 [ 25 ]. We therefore monitored the impact that 10–300 nM GZD-824 had on basal mitophagy in previously generated wild type, LRRK2[G2019S] knock-in and LRRK2 knock-out MEFs [ 7 ] stably expressing the mito -QC mitophagy reporter [ 25 ]. The mito -QC reporter is localized to mitochondria via an outer mitochondrial membrane targeting sequence derived from the protein FIS1 and bears a tandem GFP and mCherry tag.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations